Considering hydrocyclone operation for tailings dewatering purpose and its effects on product specifications of paste backfill operations. (1st November 2021) - Toprak, Nurettin Alper; Altun, Okay
Highlights: Possible use of hydrocyclone in dewatering circuit was investigated. Laboratory experiments were conducted prior to the modelling. Cyclone selection methodology and modelling-simulation helped to select the geometry of pilot scale unit. The plant implemented cyclone operation and the product specifications were enhanced. Cement consumption was reduced by 15% that is expected to contribute overall economy. Abstract: Tailings management is challenging and important task especially for the plants that are considering to utilize them. Cemented paste backfill (CPB) can be counted as one of them where the opportunities regarding to economy improvement exist. Within the CPB application, dewatering of the product is of crucial importance where thickeners are mostly preferred. However, alternative solutions should also be considered to improve the solid concentration, throughput and maybe the product specifications. The aim of this study was to improve the knowledge regarding to the use of dewatering cyclone in copper concentration plant. In this operation, the tailings are initially sent to thickener and then mixed with cement-water mixture prior to its use in the underground mining. Data collection aimed at testing of varied cyclone geometries to define the limits of the laboratory unit. Afterwards, the modelling studies were performed for a given geometry and scaling up was completed to suggest pilot scale unit. Initial studies were followed by the pilot scale trials where the product properties such as strength and viscosity were considered. As a result of the study, cyclone application was found to improve the strength of CPB material with reduced cement consumption and reduced viscosity in comparison to that of the thickening process.